2020
DOI: 10.3390/ma13184187
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Susceptibility and Allergy Potential of Austenitic Stainless Steels

Abstract: Although called stainless steels, austenitic steels are sensitive to localized corrosion, namely pitting, crevice, and intergranular form. Seventeen grades of steel were tested for localized corrosion. Steels were also tested in general corrosion and in galvanic couplings (steels–precious alloys) used in watchmaking applications. The evaluations have been carried out in accordance with the ASTM standards which specifically concern the forms of corrosion namely, general (B117-97, salt fog test), pitting (G48-11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Our previous studies showed that the transverse surface is clearly more sensitive than the longitudinal one in the rolling direction [16][17][18], a fact also supported by Nickel release tests [16][17][18].…”
Section: Detection Of Susceptibility To Intergranular Corrosion (The Strauss Test)mentioning
confidence: 62%
“…Our previous studies showed that the transverse surface is clearly more sensitive than the longitudinal one in the rolling direction [16][17][18], a fact also supported by Nickel release tests [16][17][18].…”
Section: Detection Of Susceptibility To Intergranular Corrosion (The Strauss Test)mentioning
confidence: 62%
“…Corrosion rate was determined via potentiostate (G 750) using the simulated body fluid (SBF) solution having 7.4 pH in the voltage range of −0.3 to 0.3 V. The composition of the SBF was prepared according to the kukuboo recipe as given in Table 3 [51]. Preparation of samples (i.e., the working electrodes) were done by following ASTM G108-94 standard [52] and analyzed at 37 • C as shown in Figure 3. Tafel curves were plotted at a rate of 1 mv/sec to find the current-density and potential.…”
Section: Corrosion Testingmentioning
confidence: 99%
“…The different manufacturing processes and operations of austenitic steel definitely have an impact on the quantities of nickel released. For example, an important variation in the quantities of Ni released from steels [9,10] was associated with the chemical composition, which depends majorly on the manufacturer. The nickel ions release can be controlled through heat treatments.…”
Section: Introductionmentioning
confidence: 99%